The Influence of Socioemotional Wealth on Entrepreneurial Orientation and Business Performance in Family Business - Ni Made Erina Arya Puspita (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
This research aims to analyze the influence of Socioemotional Wealth and Entrepreneurial Orientation towards Business Performance of Family Business. The background of this research is the decline of family businesses, especially when passing over to the second generation, due to the lack of attention of succession in the family businesses' long-term orientation. Thus, Socioemotional Wealth and Entrepreneurial Orientation are suggested to provide significant influence on the family businesses' Business Performance, especially in helping to maintain and passing the succession to the next generation. This research is a quantitative research analyzed using SEM-PLS. questionnaire The data is gathered from 60 respondents, who are members of UC Family Business Community, using online questionnaire with likert scale, and is calcultated using sampling method called "Rule of Thumb". The independent variables of this research are Socioemotional Wealth and Entrepreneurial Orientation, and the dependent variables of this research are Entrepreneurial Orientation and Business Performance. The result indicates Socioemotional Wealth has positive and significant influence towards Entrepreneurial Orientation and Business Performance, and Entrepreneurial Orientation has positive and significant influence towards Business Performance.